Examining functional sexual and reproductive health and right-based friendly services: perspectives from exit adolescents, caregivers, and health workers at health services delivery points in Tanzania - Gerald Kihwele; Michael Nienga Mbele; Walter C. Millanzi (BMC Health Services Research)
Abstract Background The lack of adequate access to and use of sexual and reproductive health care by youth and adolescent, n low- and middle-income countries persists despite international accords on their rights, which exposes them to violence against children; early and unintended pregnancies; and sexually transmitted infections. This study examined functional sexual and reproductive health and right-based friendly services as perceived by exit male and female adolescents, caregivers, and health workers at the Tanzanian health services delivery points as they were the ones who would share their opinions to establish a diversified and representative reality about the matter based on sex. Methods This was a multicentric study among 205 randomly selected participants in eleven selected health facilities within the three regions of Tanzania including Dar es Salaam, Dodoma, and Kigoma regions using a one-time descriptive cross-sectional design with a quantitative research approach from 01 to 30 November 2022. Triangulation technique of data collection activities using structured questionnaires and observation checklist adopted from the Tanzanian Ministry of Health was used to collect data. IBM Statistical Package for Social Sciences version 26 data entry templates (Sa PSS – 26) were used to analyze data descriptively to establish frequencies and percentages. Results Results indicated that 205 participants were assessed in this study with a response rate of 100%. Exit adolescents (46%); health workers in dispensaries (60%), and community members (42%) were more likely to confirm the availability of functional SRH right-based adolescent and youth-friendly services at the health services delivery points. The SRH displays (50%); adolescent rights (6%) and confidentiality (5%) were the least reported functional SRH aspects by the study participants. It was noted that the 11 health services delivery points in their totality did not fully implement the National standards in providing the services to adolescents and youth of which standards III (54.0%) and VIII (46.1%) scored the lowest. Conclusion The results of this study have uncovered that there is disperities in the availability and accessibility of functional SRH right-based adolescent and youth-friendly services across the levels of health facilities; among adolescents and community members. Hospitals were more likely to confirm the availability of Functional Right Based Youth Friendly Services than at health centers and dispensaries with female adolescents, youth, and community members being disadvantaged. There is a need to address issues of differentials in equity to the accessibility of services among adolescents, youth, and community members by improving functional sexual and reproductive health and right-based friendly services provision infrastructures, health care workers capacity building, and mechanisms or approaches to increase adolescents’ access and uptake to SRHR services.